Extrafollicular adenomatoid odontogenic tumor in the maxillary incisor region disguised as gingival swelling - Natasha Saini; Bindu Kadian; Tanu Rajain; Saurabh Narang; Ritu Namdev (Wolters Kluwer Medknow Publications, 2020)
Adenomatoid Odontogenic Tumor (AOT) is a benign, non-invasive tumor with slow but progressive growth, mainly affecting younger patients, predominantly females. It is more often located in maxilla, involving an unerupted or erupted tooth, mostly canine. There are three variants, namely follicular, extra-follicular and peripheral. Permanent cuspids account for 60% of all follicular and 89% of all extra-follicular AOT. This article discusses a unique case of extra-follicular AOT in 9 year old male patient associated with partially erupted maxillary central incisor.